(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
The stem bark of Grewia venusta and the flower sepal of Bombax costatum, two mucilaginous plants, were investigated as potential sources of bioadhesives for formaldehyde-free particleboards. Mucilage and pectin fractions of both plant organs were analysed for monosaccharides identification and quantification. The binding properties of these mucilages were investigated by testing mechanically particleboard made with the extracted mucilages. The aqueous extraction and ethanolic precipitation, followed by ionic chromatography gave the following results. Depending on the plant organ, extraction yield varied from 12% to 45 %. The pectin from B. costatum contained mainly rhamnose and arabinose (85%), while G. venusta bark’s pectin enclosed basically arabinose, glucose and fucose (80%). The mechanical behaviour of the panels met most of the requirements of ANSI 208.1 standard. Keywords: Bombax costatum, Grewia venusta, Pectin, Mucilage and Monosaccharides DOI: 10.3329/bjsir.v44i2.3681 Bangladesh J. Sci. Ind. Res. 44(2), 247-253, 2009